Estudo de proteção elétrica de uma microrrede baseada na rede de 34 barras do IEEE - Israel Resende Alves Rodrigues (2017)
This work is dedicated to investigate the main challenges found in the digital protection of medium-voltage, alternating current microgrids. Initially, a literature review is carried out on pilot microgrids working in Brazil and abroad, as well as on normative issues about the topic. Protection philosophies and algorithms proposed in technical papers are also presented and discussed. The impact of a microgrid on the conventional distribution protection philosophy, based on unidirectional power flow and high fault/nominal current ratio, is of concern. It is shown that a conventional protection scheme is not able to safeguard the selectivity and coordination in microgrids, including off-grid operation. The IEEE 34 bus test feeder was adapted to include distributed generation inside a delimited area that was assumed to be able to work on-grid and off-grid as a microgrid. This network was implemented in the ATP program, and the voltage and current phasors under several fault conditions were calculated. The calculated phasors helped understanding the protection issues caused by the microgrid operation. They were also used as a reference for the proposal of an effective protection scheme for the modeled microgrid. The results show the challenges in assuring the required sensitivity and selectivity of a protection system based on inverse time overcurrent units for all the operative conditions imposed by microgrids. Algorithms like the differential protection, which benefits from the exchange of information between digital relays, are capable to adapt to all scenarios in which a microgrid may operate. Backup protection schemes based only on local measurement shall be used in the event of unavailability of the communication channel among digital relays.